Covid-19 Health Education for Compliance in Implementing Health Protocols - Andri Setyorini; Musdalifah; Sri Nur Hartiningsih (Caring: Indonesian Journal of Nursing Science, 2023)
The Covid-19 pandemic has forced people to fight hard to survive and adapt to a lifestyle in the new normal era. To adapt to the new normal era, complying with health protocols is needed to reduce the transmission rate of positive cases. Thus, continuous promotive efforts must be carried out to increase awareness and healthy living behaviour in the community. This study aims to determine the effect of health education about Covid-19 on adherence to implementing health protocols. This research is pre-experimental. Sampling used the Total Sampling technique with 20 women in Trimurti Village RT.08 Kapanewon Srandakan. The instrument used is a compliance questionnaire adopted from Istikomah (2021). The analytical test used is the Wilcoxon test. These study results illustrate that most adherents to carrying out health protocols before being given health education were in the moderately obedient category, namely 17 respondents (85%). Meanwhile, most adherents to implementing health protocols for mothers after being given health counselling were in the obedient category, namely 17 respondents (85%). The results of data analysis using the Wilcoxon test show the results of Signed Ranks, namely z count ≤ z table (109.00 ≤ -3.742), with a sig value of ≤0.000. It can be concluded that health education about Covid-19 influences mothers' attitudes and compliance in implementing health protocols.